Prevalence of gestational diabetes among the women attending the OPD of a selected tertiary level hospital in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Diabetes is a serious and growing global epidemic affecting people more in developing countries than developed countries, and is particularly devastating when triggered during pregnancy. Women with GDM are at increased risk of developing type 2 diabetes mellitus after pregnancy, while their offspring are prone to develop childhood obesity with type 2 diabetes in later life. This study was aimed to estimate the prevalence of gestational diabetes in Bangladeshi women. A descriptive cross-sectional study was carried out to estimate the prevalence of Gestational Diabetes among the pregnant women attending the OPD of BIRDEM Hospital. The study was conducted from January 2013 to April 2013. A non-probability purposive sampling technique was used. The data was collected using pre-tested self-administered semi-structured questionnaire and collected data was analyzed using SPSS 22.0 version. The finding of this study shows that, 42.3% of the respondents were in the age group 30-34 years and the mean age of the respondents was 24.4 (±4.94) years. The majority of the respondents (68.2%) were Muslim and it was also seen that 46.9% of the respondents had HSC level of education. More than half (65.9%) of the respondents were housewives and about 82.9% were from nuclear family. About 47.3% of the respondents had positive family history of hypertension and 34.4% had diabetes. More than half (57.7%) of the respondents did not maintain diabetic diet and 23.6% of the respondents had attended GDM program. The prevalence of gestational diabetes is 35.1%. There is need of appropriate intervention to control GDM and also risk indicator modifications in order to avoid complication regarding to mother and child.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 116-121